Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's evaluate each equation step-by-step to determine if it is true or false.
Equation A: [tex]\(-7 - 5 + 3 = 1\)[/tex]
1. Start with [tex]\(-7 - 5\)[/tex]:
[tex]\[-7 - 5 = -12\][/tex]
2. Now, add 3:
[tex]\[-12 + 3 = -9\][/tex]
3. Therefore, [tex]\(-7 - 5 + 3 = -9\)[/tex], not 1.
So, equation A is False.
Equation B: [tex]\(-(9 + 11) + 1 = -1\)[/tex]
1. First, evaluate the expression inside the parentheses:
[tex]\[9 + 11 = 20\][/tex]
2. Now, apply the negative sign:
[tex]\[-(20) = -20\][/tex]
3. Add 1:
[tex]\[-20 + 1 = -19\][/tex]
4. Therefore, [tex]\(-(9 + 11) + 1 = -19\)[/tex], not -1.
So, equation B is False.
Equation C: [tex]\(24 - (-6) - 6 = 24\)[/tex]
1. Start with the subtraction of a negative number (which is equivalent to adding):
[tex]\[24 - (-6) = 24 + 6 = 30\][/tex]
2. Now, subtract 6:
[tex]\[30 - 6 = 24\][/tex]
3. Therefore, [tex]\(24 - (-6) - 6 = 24\)[/tex].
So, equation C is True.
Equation D: [tex]\(12 + (-8) - 1 = 3\)[/tex]
1. Add -8 to 12:
[tex]\[12 + (-8) = 4\][/tex]
2. Then, subtract 1:
[tex]\[4 - 1 = 3\][/tex]
3. Therefore, [tex]\(12 + (-8) - 1 = 3\)[/tex].
So, equation D is True.
Equation E: [tex]\(-|2 - 7| + 5 = 0\)[/tex]
1. First, calculate the absolute value:
[tex]\[2 - 7 = -5\][/tex]
[tex]\[|-5| = 5\][/tex]
2. Apply the negative sign:
[tex]\[-|2 - 7| = -5\][/tex]
3. Add 5:
[tex]\[-5 + 5 = 0\][/tex]
4. Therefore, [tex]\(-|2 - 7| + 5 = 0\)[/tex].
So, equation E is True.
Based on the evaluations:
- Equation A: False
- Equation B: False
- Equation C: True
- Equation D: True
- Equation E: True
Here’s the final categorization:
A [tex]\(\square\)[/tex] False
B [tex]\(\square\)[/tex] False
C [tex]\(\square\)[/tex] True
D [tex]\(\square\)[/tex] True
E [tex]\(\square\)[/tex] True
Equation A: [tex]\(-7 - 5 + 3 = 1\)[/tex]
1. Start with [tex]\(-7 - 5\)[/tex]:
[tex]\[-7 - 5 = -12\][/tex]
2. Now, add 3:
[tex]\[-12 + 3 = -9\][/tex]
3. Therefore, [tex]\(-7 - 5 + 3 = -9\)[/tex], not 1.
So, equation A is False.
Equation B: [tex]\(-(9 + 11) + 1 = -1\)[/tex]
1. First, evaluate the expression inside the parentheses:
[tex]\[9 + 11 = 20\][/tex]
2. Now, apply the negative sign:
[tex]\[-(20) = -20\][/tex]
3. Add 1:
[tex]\[-20 + 1 = -19\][/tex]
4. Therefore, [tex]\(-(9 + 11) + 1 = -19\)[/tex], not -1.
So, equation B is False.
Equation C: [tex]\(24 - (-6) - 6 = 24\)[/tex]
1. Start with the subtraction of a negative number (which is equivalent to adding):
[tex]\[24 - (-6) = 24 + 6 = 30\][/tex]
2. Now, subtract 6:
[tex]\[30 - 6 = 24\][/tex]
3. Therefore, [tex]\(24 - (-6) - 6 = 24\)[/tex].
So, equation C is True.
Equation D: [tex]\(12 + (-8) - 1 = 3\)[/tex]
1. Add -8 to 12:
[tex]\[12 + (-8) = 4\][/tex]
2. Then, subtract 1:
[tex]\[4 - 1 = 3\][/tex]
3. Therefore, [tex]\(12 + (-8) - 1 = 3\)[/tex].
So, equation D is True.
Equation E: [tex]\(-|2 - 7| + 5 = 0\)[/tex]
1. First, calculate the absolute value:
[tex]\[2 - 7 = -5\][/tex]
[tex]\[|-5| = 5\][/tex]
2. Apply the negative sign:
[tex]\[-|2 - 7| = -5\][/tex]
3. Add 5:
[tex]\[-5 + 5 = 0\][/tex]
4. Therefore, [tex]\(-|2 - 7| + 5 = 0\)[/tex].
So, equation E is True.
Based on the evaluations:
- Equation A: False
- Equation B: False
- Equation C: True
- Equation D: True
- Equation E: True
Here’s the final categorization:
A [tex]\(\square\)[/tex] False
B [tex]\(\square\)[/tex] False
C [tex]\(\square\)[/tex] True
D [tex]\(\square\)[/tex] True
E [tex]\(\square\)[/tex] True
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.